Forced vibration characteristics of sandwich panel with GRPC faces and titanium core under thermal environment. (2022) - Sivajiraja, Golla; Bhagat, Vinod; Padhi, S.N.; Arunkumar, M.P.; Dessai, Amey Naik; Kiran Kumar Reddy, R.
Abstract: In this paper forced vibration characteristics of a graphene reinforced polymer composite face sheet sandwich panel with a homogeneous core exposed to non-uniform temperature variation is studied. Carbon based materials are highly used in aerospace applications. Further these materials are exposed to different environmental conditions which alters it dynamic characteristics. So, in this paper thermal buckling and forced vibration behavior are studied for different grading patterns, temperature dependent properties and non uniform temperature variation. Here, uniform temperature profile, decreasing temperature profile - heating at one edge, decreasing and increasing temperature profile - heating at two edges, increasing and decreasing temperature profile - heating at middle and camel hump temperature - heating at Centre location of the panels are considered. From the results, it is observed that the temperature distribution at 95% of buckling temperature has reduced the natural frequencies significantly and in the forced vibration response, the sandwich panel in this condition shifts its response curve to the left irrespective of the grading pattern. Further, it is noticed that the velocity response curve of FG-X grading pattern has shifted more compare to UD and FG-O grading pattern.